The Effect of Snowball Throwing Learning Model on Learning Outcomes of Aqidah Akhlak in Madinatul Ulum Islamic Elementery School - Imrie Purwa Hidayah; Hilyah Ashoumi (SCHOOLAR: Social and Literature Study in Education, 2024)
This research examines the Aqidah Akhlak learning process in the fifth grade of Madrasah Ibtidaiyah Madinatul Ulum Tembelang Jombang, which is still having difficulty in improving student learning outcomes. The main problem identified is the low enthusiasm of students and the use of conventional learning methods. To overcome this, a learning model is needed that can increase the enthusiasm for learning and understanding of students, one of which is the snowball throwing learning model. This study aims to determine the effect of snowball throwing learning model on Aqidah Akhlak learning outcomes on the material of infaq and sadaqah in the fifth grade of Madrasah Ibtidaiyah Madinatul Ulum Tembelang Jombang. This study used an experimental method with a "One-Group Pretest-Posttest" design. In this design, one group of subjects is given a pretest. The experimental group consisted of twenty-four students of class Five B, and the research was conducted for two meetings. The results of descriptive analysis showed an increase in Aqidah Akhlak learning outcomes after the application of the snowball throwing learning model. Inferential statistical analysis using the t test with the help of SPSS 21 software shows that the significance value obtained is 0.000. Because this value is smaller than the significant level of 5% or 0.05 or 0.000, the null hypothesis (HO) is rejected. This shows that the application of the snowball throwing learning model has a positive influence on the learning outcomes of Aqidah Akhlak on the material of infaq and sadaqah in class V MI Madinatul Ulum Tembelang Jombang